2013
DOI: 10.1016/j.bbmt.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Genital Chronic GVHD in Men after Hematopoietic Stem Cell Transplantation: A Single-Center Cross-Sectional Analysis of 155 Patients

Abstract: We assessed the prevalence and clinical features of genital skin changes in men after allogeneic hematopoietic stem cell transplantation (HSCT) and evaluated the correlation between genital chronic graft-versus-host disease (cGVHD) and other manifestations of cGVHD as well as sexual issues. In a cross-sectional cohort study, 155 male recipients alive 1 year or more after HSCT were assessed during their annual follow-up evaluation. Correlation between genital skin changes and other cGVHD manifestations was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 29 publications
1
33
1
1
Order By: Relevance
“…Patients may report painful sexual intercourse and a burning sensation. Genital signs of GVHD include non-infectious balanoposthitis, lichen sclerosus-like or lichen planus-like features, phimosis, or urethra or meatus scarring or stenosis 35,36 .…”
Section: Genitaliamentioning
confidence: 99%
See 1 more Smart Citation
“…Patients may report painful sexual intercourse and a burning sensation. Genital signs of GVHD include non-infectious balanoposthitis, lichen sclerosus-like or lichen planus-like features, phimosis, or urethra or meatus scarring or stenosis 35,36 .…”
Section: Genitaliamentioning
confidence: 99%
“…Genitalia: Scoring is now based on severity of the signs instead of symptoms, based on limited available data 29,31,35,36 and the opinions of experts (Supplemental Figure 1 represents an exploratory measure to be completed by specialists or trained practitioners). Female or male genital GVHD is not scored if a practitioner is unable to examine the patient.…”
Section: Clinical Scoring Of Organ Systemsmentioning
confidence: 99%
“…Over 40% of females remain sexually inactive even 5 years after treatment [167], and chronic GVHD increases this risk for both men and women [168]. Contributing factors include GVHD of the skin and genitalia, hormonal changes, and glucocorticoid therapy [147,169]. Phosphodiesterase type 5 inhibitors for men and brief therapeutic options for sexual dysfunction in this population are understudied but are beginning to demonstrate efficacy in other cancer populations [170172].…”
Section: Psychosocialmentioning
confidence: 99%
“…26 TBI has been reported to play a central role in male and female infertility in several studies, with a more profound effect noted in men. 12,27,28 Long-term effects on the hypothalamic-pituitary-gonadal axis from conditioning regimens can cause vaginal dryness, dyspareunia, and premature ovarian insufficiency in women. The incidence of premature ovarian failure after HSCT ranges from 40% to 100%.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that graft-versus-host disease (GVHD) and conditioning regimens, including chemotherapies and total body irradiation (TBI), may play a direct or indirect role in sexual health after transplantation. 7,11,12 Documented complications affecting sexuality include decreased libido, genital GVHD, hormonal dysfunction, erectile dysfunction (ED), dyspareunia, and infertility. 1113 In addition to physical health conditions, psychosocial problems also may contribute to sexual dysfunction in survivors of HSCT.…”
Section: Introductionmentioning
confidence: 99%